1985
DOI: 10.1051/jphyscol:198510156
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Dependence of the Ultrasonic Attenuation and Resistance of a Superconducting Granular Lead Film

Abstract: We report on the measurements of the ultrasonic attenuation and the d.c. resistance of a superconducting granular lead film as a function of both temperature and applied magnetic field. In the absence of an applied magnetic field, the d.c. resistance and ultrasonic attenuation can be accounted for, qualitatively, by using percolation theory. When a magnetic field is applied, we find that if we assume that both the ultra-sonic attenuation and the resistivity are proportional to the effective area through which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The situation at the Si interface is far less clear and is affected by the nature of the Si surface, i.e., if it is the native oxide or if it is passivated with HF . If it is assumed that the segregation at both interfaces (air and substrate) is similar to that predicted at the air surface by the mean-field theory of Schmidt and Binder with surface energy parameters from ref , the maximum shift in the phase separation temperature can be estimated. The film was modeled by layers of homogeneous composition parallel to the film surface with incremental changes in the composition between layers used to approximate the composition profile normal to the surface as predicted by Schmidt and Binder.…”
Section: Resultsmentioning
confidence: 99%
“…The situation at the Si interface is far less clear and is affected by the nature of the Si surface, i.e., if it is the native oxide or if it is passivated with HF . If it is assumed that the segregation at both interfaces (air and substrate) is similar to that predicted at the air surface by the mean-field theory of Schmidt and Binder with surface energy parameters from ref , the maximum shift in the phase separation temperature can be estimated. The film was modeled by layers of homogeneous composition parallel to the film surface with incremental changes in the composition between layers used to approximate the composition profile normal to the surface as predicted by Schmidt and Binder.…”
Section: Resultsmentioning
confidence: 99%
“…Spinodal decomposition of polymer blends leading to patterned phase morphologies in the bulk is a fascinating subject that has been studied for the past two decades. More recently, it has been realized that the presence of a surface breaks the rotational and translational symmetry, thus strongly altering both the equilibrium phase morphology and the phase separation kinetics. Binary mixtures of polymers (for example, deuterated poly(ethylene propylene) (dPEP) and poly(ethylene propylene (hPEP)) are useful model systems to study these effects. For example, in a film of a two-phase isotopic polymer blend on a silicon substrate, preferential adsorption of the dPEP component to the surface and hPEP to the silicon leads to the formation of a macroscopic bilayer with the dPEP-rich phase wetting the surface and the hPEP-rich phase wetting the silicon. , In the early stages oscillatory composition profiles originate from both the surface and the substrate and propagate into the bulk of the film. For compositions near the critical value, the wetting layer thickens as a + bt 1/3 where t is the time after the quench, consistent with a process controlled by diffusive material exchange across the layer. , For off-critical quenches where the majority component wets the surface, the wetting layer grows faster, its thickness increasing approximately linearly with t . These kinetics are attributed to hydrodynamic transport by flow of dPEP through a perforated layer of hPEP-rich domains just below the dPEP-rich wetting layer. …”
Section: Introductionmentioning
confidence: 99%
“…The surface chemical composition of polymer blends has been extensively investigated in the past decade, both experimentally and theoritically. Most studies revealed that the lower surface free energy γ component was enriched at the air−polymer interface in order to minimize the magnitude of interfacial free energy. For instance, in the case of the miscible polystyrene/poly(vinyl methyl ether) (PS/PVME) blend film, X-ray photoelectron spectroscopic (XPS) and surface tension measurements revealed that the surface was covered with PVME chains with lower γ. , Also, in the case of the (PS/deuterated PS) blend film, it was revealed from dynamic secondary ion mass spectroscopic (DSIMS) and forward recoil elastic scattering (FRES) measurements that deuterated PS was preferentially segregated at the film surface, since the magnitude of γ for deuterated PS is lower than that of PS due to the lower polarizability of the C−D bond compared with that of the C−H one …”
Section: Introductionmentioning
confidence: 99%